Prospects Of Use And Processing Of Titanium Blanks Obtained By xBeam 3D Metal Printing Technology - Pirohov, Dmytro; Vorontsov, Borys (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The article presents the new range of additive technologies called xBeam 3D metal printing that allows the production of titanium alloy parts for the medicine, aeronautical and automotive industries. The new technology opens up essential challenges, such as identifying and analysing the optimal finishing machining strategies for this type of part. The article analyses the production and machining of TI6Al4V produced by Wire Arc. The research focuses on implementing optimal cutting modes to obtain the required surface quality. This article provides a better understanding of the machining of titanium blanks using this technology. The optimistic results make this method the best alternative to traditional casting technologies and powder metallurgy.